Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Temperature dependent structural studies and magnetic properties of BaCa2Fe16O27 hexaferrites prepared by stearic acid gel route in presence of SDS surfactant - Joyania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Kulkarni, B. D. (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2008)
The preparation of BaCa2Fe16O27 hexaferrite powders by a stearic acid gel method with SDS surfactant has been investigated at various sintering temperatures. The samples were characterized by X-ray diffraction, scanning electron microscopy (SEM), TGA, FTIR and vibrating sample magnetometer (VSM). The effect of sintering temperature on properties of BaCa2Fe16O27 hexaferrites was studied. In presence of sodium dodecyl sulfate (SDS) surfactant, the magnetic parameters, like saturation magnetization, coercivity and remanent magnetization, have been calculated from hysteresis loop.
Symposium on New Routes to Inorganic Materials, Films and Nanocrystals held at ICMAT 2007, Singapore, SINGAPORE, JUL 01-06, 2007
Keywords: BaCa2Fe16O27; magnetic properties; stearic acid gel method